Clinical Validation of ADAM9 as a Prognostic Biomarker in Oral Cancer - Lu, Jeng‐Wei; Shih, Pei‐Chen; Chuang, Show‐Mei; Tu, Wan‐Jung; Tsai, Ming‐Heng; Tsai, Yun‐Jung; Lin, Shu‐Hui (Oral diseases, 2025)
Oral cancer has a high incidence in Taiwan, and identifying prognostic biomarkers is crucial. This study investigated the role of a disintegrin and metalloprotease 9 (ADAM9) in oral cancer progression and outcomes. This study investigated ADAM9 protein expression in 353 oral cancer tissue specimens through immunohistochemical (IHC) analysis. The analysis revealed that, among the 353 patients, 21 (6%) exhibited low ADAM9 expression, while the remaining 332 patients (94%) showed high ADAM9 expression, which correlated with advanced T status, poor overall survival, and unfavorable prognosis. Kaplan-Meier analysis confirmed that higher ADAM9 expression predicted significantly worse survival. Univariate and multivariate analyses identified ADAM9, histological grade, and AJCC stage as independent prognostic factors. Functionally, ADAM9 silencing in SAS and OC2 cells inhibited invasion and migration, downregulating matrix metalloproteinase 9 (MMP9) and matrix metalloproteinase 14 (MMP14). siRNA-mediated ADAM9 knockdown also reduced cell viability and migration, as confirmed by cell counting kit-8 and transwell assays. The Cancer Genome Atlas (TCGA) analysis further revealed a positive correlation between ADAM9 mRNA levels and matrix metalloproteinase 2 (MMP2) or MMP14 expression in oral cancer patients. This study identifies ADAM9 as a key driver of oral cancer in a Taiwanese cohort and highlights its diagnostic and therapeutic potential.